Pólis “Politica e nichilismo” ‒ per lumi sparsi - Vitiello, Vincenzo (Bollettino Filosofico, 2015)
Reconstruction by ‘scattered fragments’ of the history of Europe, from myth to contemporary political philosophy, following the concept of the Polis as the mediation place in the conflict between law and violence. Mediation impossible, because the very origin of the law is just the violence, that it should regulate. Of this impossibility the contemporary nihilism is the awareness; the modern Metropolis – of which Vitiello depicts the ‘peculiar’ logic – is the actual experience. The conflicts of our time testify with the evidence of facts the great difficulty in accepting this ‘new’ logic.